Offsetting strength loss in concrete via ITZ enhancement: From the perspective of utilizing new alternative aggregate. (March 2022) - Chen, Rumeng; Mo, Kim Hung; Ling, Tung-Chai
Abstract: In this work, the strength and microstructural changes in the interfacial transition zone (ITZ) of four individual concrete mixes containing four different materials (natural aggregate (NA), recycled concrete aggregate (RA), ceramsite (CA), and carbonated steel slag aggregate (SSA)) as 100% coarse aggregate replacement were investigated. The major takeaway from this work is the formation of better quality ITZ due to the use of carbonated SSA, as reflected by the higher microhardness and denser microstructure. The presence of calcite on the outer surface of SSA helps to form monocarbonate and serves as nucleation site for growth of calcium silicate hydrates, enabling a reduction in porosity and calcium hydroxide content by 56% and 80%, respectively compared to the NA concrete. As a result, SSA concrete achieved similar 28-day compressive strength as the NA concrete. This excitingly brings a new insight into how enhancement of the ITZ region could fully compensate the lower intrinsic strength of alternative aggregate used in the concrete. Highlights: Reduced porosity and Ca(OH)2 in the ITZ of carbonated steel slag aggregate (SSA) concrete. Comparable ultimate strength between normal and SSA concrete. Highest Vickers hardness for ITZ of SSA concrete. ITZ properties dictated by mineralogy rather than thickness.